Adaptation of Lettuce mosaic virus to Catharanthus roseus Involves Mutations in the Central Domain of the VPg - Laurence Svanella-Dumas; Eric Verdin; Chantal Faure; Sylvie German-Retana; Patrick Gognalons; Jean Luc Danet; Armelle Marais; Thierry Candresse (Molecular Plant-Microbe Interactions, 2014)
An isolate of Lettuce mosaic virus (LMV, a Potyvirus) infecting Madagascar periwinckle (Catharanthus roseus) was identified and characterized by Illumina deep sequencing. LMV-Cr has no close affinities to previously sequenced LMV isolates and represents a novel, divergent LMV clade. Inoculation experiments with other representative LMV isolates showed that they are unable to infect C. roseus, which was not known to be a host for LMV. However, three C. roseus variants of one of these isolates, LMV-AF199, could be selected and partially or completely sequenced. These variants are characterized by the accumulation of mutations affecting the C-terminal part of the cylindrical inclusion (CI) helicase and the central part of the VPg. In particular, a serine to proline mutation at amino acid 143 of the VPg was observed in all three independently selected variants and is also present in the LMV-Cr isolate, making it a prime candidate as a host-range determinant. Other mutations at VPg positions 65 and 144 could also contribute to the ability to infect C. roseus. Inoculation experiments involving a recombinant LMV expressing a permissive lettuce eukaryotic translation initiation factor 4E (eIF4E) suggest that eIF4E does not contribute to the interaction of most LMV isolates with C. roseus.